2008
DOI: 10.1021/ma8018365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu(0) Particle Size on the Kinetics of SET-LRP in DMSO and Cu-Mediated Radical Polymerization in MeCN at 25 °C

Abstract: In order to estimate the effect of Cu(0) particle size in SET-LRP, a comparative analysis of Cu(0)/ Me 6 -TREN-catalyzed polymerization of MA initiated with methyl 2-bromopropionate at 25 °C was performed in DMSO, a solvent that mediates the disproportionation of Cu(I)X, and in MeCN, a solvent in which Cu(I)X does not disproportionate Cu(I)X. Decreasing the Cu(0) particle size results in a marked increase in the apparent rate constant of propagation (k p app ). Decreasing the Cu(0) particle size from 425 to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
263
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(270 citation statements)
references
References 24 publications
7
263
0
Order By: Relevance
“…10 42 exhibit amplified adsorption and desorption processes that may complement the previous studies on the elucidation of the role of the surface of Cu(0) catalyst on the activation and deactivation steps of SET-LRP. 11,[58][59][60][61] This publication reports the aqueous SET-LRP of HEA and OEOMEA mediated by "in situ" generated Cu(0) catalyst. 26,37,38 The study reported here demonstrates that the surface of Cu(0) is responsible both for the activation of the initiator and dormant growing species, as well as for the much lower extent of bimolecular termination observed during polymer synthesis by SET-LRP.…”
Section: Introductionmentioning
confidence: 99%
“…10 42 exhibit amplified adsorption and desorption processes that may complement the previous studies on the elucidation of the role of the surface of Cu(0) catalyst on the activation and deactivation steps of SET-LRP. 11,[58][59][60][61] This publication reports the aqueous SET-LRP of HEA and OEOMEA mediated by "in situ" generated Cu(0) catalyst. 26,37,38 The study reported here demonstrates that the surface of Cu(0) is responsible both for the activation of the initiator and dormant growing species, as well as for the much lower extent of bimolecular termination observed during polymer synthesis by SET-LRP.…”
Section: Introductionmentioning
confidence: 99%
“…17,61,62 More recently, Percec and co-workers proposed that the Cu(0)-based living radical polymerization proceeds via a single-electron transfer mechanism under certain conditions and that their systems are highly effective for the very fast living radical polymerization of various monomers, leading to well-controlled high-molecular weight polymers with narrow MWDs. [63][64][65][66] In contrast, the Cu(I)-based systems in the presence of reducing agents, such as tin(II) 2-ethylhexanoate, ascorbic acid, Cu(0) and radical initiators, also induced an efficient living radical polymerization, in which the accumulated Cu(II) species changed into the active Cu(I) species via the reduction by these additives. [67][68][69][70] Although the working mechanisms of Cu(0) are still controversial and may depend on the conditions, it is clear that the use of lower oxidation metal species is important for constructing highly catalytic systems.…”
Section: Metal Catalytic Systemsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The simple and highly versatile SET-LRP process based on the catalysis by Cu(0) powder or wire is remarkably effective for synthesis of polyacrylate. [10][11][12][13][14][15][16][17] As we all know, the LRP is the significant and useful procedure to synthesize polymers with controlled molecular weight and narrow molecular weight distribution. However, it has been accomplished only for activated monomers.…”
Section: Introductionmentioning
confidence: 99%